Gain of function mutant p53 protein activates AKT through the Rac1 signaling to promote tumorigenesis. Issue 11 (2nd June 2020) - Yue, Xuetian; Wu, Fangnan; Li, Yanchen; Liu, Juan; Boateng, Michael; Mandava, Kranthi; Zhang, Cen; Feng, Zhaohui; Gao, Jimin; Hu, Wenwei
ABSTRACT: Tumor suppressor p53 is the most frequently mutated gene in human cancer. Mutant p53 (mutp53) not only loses the tumor suppressive activity of wild type p53, but often gains new oncogenic activities to promote tumorigenesis, defined as mutp53 gain of function (GOF). While the concept of mutp53 GOF is well-established, its underlying mechanism is not well-understood. AKT has been suggested to be activated by mutp53 and contribute to mutp53 GOF, but its underlying mechanism is unclear. In this study, we found that the activation of the Rac1 signaling by mutp53 mediates the promoting effect of mutp53 on AKT activation. Blocking Rac1 signaling by RNAi or a Rac1 inhibitor can inhibit AKT activation by mutp53. Importantly, targeting Rac1/AKT can greatly compromise mutp53 GOF in tumorigenesis. Results from this study uncover a new mechanism for AKT activation in tumors, and reveal that activation of AKT by mutp53 via the Rac1 signaling contributes to mutp53 GOF in tumorigenesis. More importantly, this study provides Rac1 and AKT as potential targets for therapy in tumors containing mutp53.